Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1111/j.1745-493x.1993.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplier Development Programs: An Empirical Analysis

Abstract: To compete effectively in the global marketplace, a company must have a network of competent suppliers. A supplier development program is designed to create and maintain such a network—and to improve various supplier capabilities that are necessary for the buying organization to meet its increasing competitive challenges. This article discusses the results of a survey dealing with supplier development activity. The survey was undertaken to determine the current level of involvement in supplier development prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
166
0
11

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(192 citation statements)
references
References 4 publications
(4 reference statements)
10
166
0
11
Order By: Relevance
“…Our results indicate that a reciprocal relationship between buyers and suppliers causes the accumulation of relational social capital. This is consistent with the results of previous studies, which found that the GSCM system has a greater focus on developing future, long-term capabilities than on advancing current quality, cost, and environment [3,86] or building long-term partnership and loyalty to both buyers and suppliers. [65,87].…”
Section: Empirical Findings and Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results indicate that a reciprocal relationship between buyers and suppliers causes the accumulation of relational social capital. This is consistent with the results of previous studies, which found that the GSCM system has a greater focus on developing future, long-term capabilities than on advancing current quality, cost, and environment [3,86] or building long-term partnership and loyalty to both buyers and suppliers. [65,87].…”
Section: Empirical Findings and Discussionsupporting
confidence: 82%
“…The GSCM system has a greater focus on developing future, long-term capabilities than on advancing current quality or reducing current cost [3,86]. A larger extent of support and joint performances, such as training and education in addition to technical assistance along the execution of GSCM, can build long-term partnerships and loyalty for both buyers and suppliers [65,87].…”
Section: Gscm and Social Capitalmentioning
confidence: 99%
“…Supply chain management in TQM implies reducing and streamlining the supplier base to facilitate managing supplier relationships [44], developing strategic alliances with suppliers [45,46], working with suppliers to ensure that expectations are met [47], and Advances in Decision Sciences 5 involving suppliers early in the product development process to take advantage of their capabilities and expertise [48,49].…”
Section: Supplier Quality Managementmentioning
confidence: 99%
“…Once the alliance begins information quality and continuous quality improvements become important factors in the maturation of the relationship. Another implication from our findings is that greater interaction among firms may promote a sharing of resources (Watts & Hahn, 1993), which results in improved quality, reduced costs, and increased continuous improvement for all involved parties. In addition, partnerships based on a commitment to continuous improvement where SME organizations partner with more established organizations allow the SMEs to mitigate their lack of a track record of success and therefore reduce their overall likelihood of failure (Hudson & McArthur, 1994;Aldrich & Auster, 1986).…”
Section: Discussion and Practical Implicationsmentioning
confidence: 93%